Gamma radiation-induced defects in KCl, MgCl2, and ZnCl2 salts at room temperature. Issue 17 (23rd April 2021) - Ramos-Ballesteros, Alejandro; Gakhar, Ruchi; Horne, Gregory P.; Iwamatsu, Kazuhiro; Wishart, James F.; Pimblott, Simon M.; LaVerne, Jay A.
Abstract : Room temperature post-irradiation measurements of diffuse reflectance and EPR spectroscopies were made to characterize the long-lived radiation-induced species formed upon gamma irradiation (up to 100 kGy) of solid KCl, MgCl2, and ZnCl2 salts. Abstract : Room temperature post-irradiation measurements of diffuse reflectance and electron paramagnetic resonance spectroscopies were made to characterize the long-lived radiation-induced species formed from the gamma irradiation of solid KCl, MgCl2, and ZnCl2 salts up to 100 kGy. The method used showed results consistent with those reported for electron and gamma irradiation of KCl in single crystals. Thermal bleaching of irradiated KCl demonstrated accelerated disaggregation of defect clusters above 400 K, due to decomposition of Cl3 − . The defects formed in irradiated MgCl2 comprised a mixture of Cl3 −, F-centers, and Mg + associated as M-centers. Further, Mg metal cluster formation was also observed at 100 kGy, in addition to accelerated destruction of F-centers above 20 kGy. Irradiated ZnCl2 afforded the formation of Cl2 − due to its high ionization potential and crystalline structure, which decreases recombination. The presence of aggregates in all cases indicates the high diffusion of radicals and the predominance of secondary processes at 295 K. Thermal bleaching studies showed that chloride aggregates' stability increases with the ionization potential of the cation present. The characterization of long-lived radiolytic transients of pure salts provides important information for the understanding of complex salt mixtures under the action of gamma radiation.